Identifying and explaining the indicators and components of water reporting in corporate level using the Best-Worst Method - Fatemeh Asnad; Hossein Fakhari (Journal of Applied Research in Water and Wastewater, 2023)
The occurrence of global environmental crises, combined with population growth and increased global water demand, highlights the pressing need for effective management of water resources. This includes comprehensive attention to water administration, consumption, and reporting. The objective of this research is to investigate the frameworks of global water reporting and provide a robust and comprehensive model for water reporting in Iranian listed companies. To achieve this goal, a survey was conducted in 2023 involving sixteen experts in water reporting. The participants consisted of engineers and managers from prominent companies in the water consumption and sustainability reporting sector, as well as university professors specializing in sustainability studies and research. The aim was to identify the appropriate components of water reporting for companies listed on the Iran Stock Exchange. Subsequently, the Best-Worst Method (BWM), a multi-criteria decision-making approach, was employed to determine the importance of each reporting item and establish the priorities of the reporting components. The results revealed that the main components of water reporting, ranked in order of importance, are as follows: performance, business strategies, water-related impacts, metrics, water governance, risks and opportunities, and finally regulations and rights. These findings hold valuable implications for stock market policymakers and company managers. By recognizing these critical indicators and components, they can effectively mandate water reporting for Iranian listed companies. Furthermore, they can ensure that water reporting accurately reflects the significant aspects of corporate operations related to water resources.